Variation in care for infants undergoing the Stage II palliation for hypoplastic left heart syndrome - Eckhauser, Aaron (Cardiol Young, 2018)
BACKGROUND: The Single Ventricle Reconstruction trial randomised neonates with hypoplastic left heart syndrome to a systemic-to-pulmonary-artery shunt strategy. Patients received care according to usual institutional practice. We analysed practice variation at the Stage II surgery to attempt to identify areas for decreased variation and process control improvement. METHODS: Prospectively collected data were available in the Single Ventricle Reconstruction public-use database. Practice variation across 14 centres was described for 397 patients who underwent Stage II surgery. Data are centre-level specific and reported as interquartile ranges across all centres, unless otherwise specified. RESULTS: Preoperative Stage II median age and weight across centres were 5.4 months (interquartile range 4.9–5.7) and 5.7 kg (5.5–6.1), with 70% performed electively. Most patients had pre-Stage-II cardiac catheterisation (98.5–100%). Digoxin was used by 11/14 centres in 25% of patients (23–31%), and 81% had some oral feeds (68–84%). The majority of the centres (86%) performed a bidirectional Glenn versus hemi-Fontan. Median cardiopulmonary bypass time was 96 minutes (75–113). In aggregate, 26% of patients had deep hypothermic circulatory arrest >10 minutes. In 13/14 centres using deep hypothermic circulatory arrest, 12.5% of patients exceeded 10 minutes (8–32%). Seven centres extubated 5% of patients (2–40) in the operating room. Postoperatively, ICU length of stay was 4.8 days (4.0–5.3) and total length of stay was 7.5 days (6–10). CONCLUSIONS: In the Single Ventricle Reconstruction Trial, practice varied widely among centres for nearly all perioperative factors surrounding Stage II. Further analysis may facilitate establishing best practices by identifying the impact of practice variation.